Energy, unemployment and trade - Rafiq, S.; Salim, Ruhul; Sgro, P. (Routledge, 2018)
© 2018 Informa UK Limited, trading as Taylor & Francis Group. This article investigates the dynamic relationships among sectoral economic activities, macro expenditure patterns, renewable and non-renewable energy consumption and unemployment in 41 countries from 1980 to 2014. The state of the art econometric techniques, both linear and non-linear panel and time series estimation techniques are used. The results show that industrialization, services sector, government expenditure and trade openness play a positive role in reducing unemployment, while agriculture and renewable energy consumption increase unemployment. This might be, in part, due to recent technological advancements and large capital intensive investments in agriculture and renewable energy sectors. Therefore, dedicated social and labour market policies need to be adopted to complement greening economic policies.